A Review on Big Data Analytics in Healthcare Using Machine Learning Approaches - Patel, Hardik B.; Gandhi, Snehal (2018 2nd International Conference on Trends in Electronics and Informatics (ICOEI), 2018)
The rapid expansion of the business intelligence and analytics process has emphasized the importance of how knowledge is aquire and helps to make appropriate decision. The big data in area of healthcare open up new ways for analyze and aquire intelligence from big data. The conventional approaches for management of health data have archive limited success. The traditional approaches are incapable of management and process on big data because of its different characteristics. Following paper shows various techniques for process the big data as machine learning and statistics approaches. Also the paper shows the various tools for storing the big data and its advantages as well as disadvantages for health care big data.